1996
DOI: 10.1111/j.1745-6584.1996.tb02024.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Thermal‐Infrared Imagery to Delineate Ground‐Water Discharged

Abstract: On March 8 and 9, 1992, a thermal‐infrared‐multispectral scanner (TIMS) was flown over two military ordnance disposal facilities at the Edgewood Area of Aberdeen Proving Ground, Maryland. The data, collected by the National Aeronautics and Space Administration, in cooperation with the U.S. Army and the U.S. Geological Survey, were used to locate ground‐water discharge zones in surface water. The images from the flight show areas where ground‐water discharge is concentrated, as well as areas of diffuse discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 2 publications
1
43
0
Order By: Relevance
“…2(a) and (b)) (Banks et al, 1996;Torgersen et al, 2001). The visual interpretation is influenced by the interpreters' subjective factors and contains significant uncertainties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2(a) and (b)) (Banks et al, 1996;Torgersen et al, 2001). The visual interpretation is influenced by the interpreters' subjective factors and contains significant uncertainties.…”
Section: Resultsmentioning
confidence: 99%
“…Most previous studies used temperature as independent calibration data for coupled surface water and groundwater models (Brookfield et al, 2009) or analysed the surface water and groundwater interaction pattern by direct visual interpretation (Banks et al, 1996;Torgersen et al, 2001). The construction of coupled models is time consuming and the visual interpretation is always influenced by subjective factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Popular applications of handheld and infrared technology examine discrete groundwater discharge, surface water-groundwater interactions, and submarine groundwater discharge (Vivas Becerras, 2014;Deitchman and Loheide, 2009;Roeper et al, 2014;Pandey et al, 2013;Pfister et al, 2010;Schuetz and Weiler, 2011;Hare et al, 2015;Banks et al, 1996). For example, Vivas Becerras (2014) captured thermal images of the Stawamus Chief, a granite monolith in Squamish, British Columbia, and found that lower temperature values were associated with water seepage on the rock face.…”
Section: Well 281 and Well 283mentioning
confidence: 99%
“…Use of temperature has the particular advantage that it can be measured rapidly over large areas by remote thermal infrared (IR) imaging (Banks et al 1996, Lavery et al 1993, Torgersen et al 2001. In Hawai'i, infrared and multispectral imaging of the coastlines were conducted as early as the late 1960s (Adams and Lepley 1968, Fischer et al 1966, Lepley and Palmer 1967; however, little ground truthing was conducted.…”
Section: Introductionmentioning
confidence: 99%